Analisis dan Perancangan Sistem Informasi dalam Membantu UMKM dalam Memasarkan Produk - Muhammad Fadhil Risyad; Diah Priharsari; Kariyoto Kariyoto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
MSMEs are one of the drivers of the economy in Indonesia. MSMEs are the largest business units in Indonesia with a number reaching 99.9% of the total business fields (Santia, 2020). The development of MSMEs must include improvements in all aspects again in terms of sales. This increase can be achieved by digitizing MSMEs. Through the digitization process, MSMEs can optimize the opportunities and opportunities that exist because the targets that can be achieved are wider. This research is a research related to the process of optimizing MSMEs digitally. The digitization of MSMEs in this study was carried out by designing an e-MSME system. E-MSME is a system design that can help MSMEs in marketing their products. This marketing is done by providing a marketplace for MSMEs and consumers. So that consumers can find the product they are looking for according to their needs. This study uses a prototype model method that comes from the design process, using modeling using UML (Unified Modeling Language). Data collection in this research process is using data from three resource persons who are engaged in MSMEs. The next process after UML modeling is prototype design using the Figma platform. The finished prototype is then returned so that the repair process can be carried out. The results obtained from this study are the system has obtained